Year-end appeal: Please make a donation to the OEIS Foundation to support ongoing development and maintenance of the OEIS. We are now in our 61st year, we have over 378,000 sequences, and we’ve reached 11,000 citations (which often say “discovered thanks to the OEIS”).
%I #22 Sep 08 2022 08:45:57
%S 1,1,3,12,50,224,1054,5121,25509,129591,668811,3496740,18481512,
%T 98585788,530068840,2869725800,15630429306,85589391884,470905310206,
%U 2601941245750,14432082902820,80328808797750,448527122885700,2511672193514250
%N Reversion of x-x^2-x^3-2*x^4
%C For the reversion of x - a*x^2 - b*x^3 - c*x^4 (a!=0, b!=0, c!=0) we have
%C a(n) = sum(k=1,n-1, (sum(j=0..k, a^(-n+3*k-j+1)*b^(n-3*k+2*j-1)*c^(k-j)*binomial(j,n-3*k+2*j-1)*binomial(k,j)))*binomial(n+k-1,n-1))/n, n>1, a(1)=1.
%H Vincenzo Librandi, <a href="/A191242/b191242.txt">Table of n, a(n) for n = 1..200</a>
%H Vladimir Kruchinin, <a href="http://arxiv.org/abs/1211.3244">The method for obtaining expressions for coefficients of reverse generating functions</a>, arXiv:1211.3244 [math.CO], 2012.
%F a(n) = sum(k=1..n-1, (sum(j=0..k, binomial(j,n-3*k+2*j-1)*2^(k-j)*binomial(k,j)))*binomial(n+k-1,n-1))/n, n>1, a(1)=1.
%t a[1] = 1; a[n_] := Sum[Sum[Binomial[j, n - 3k + 2j - 1]*2^(k - j)* Binomial[k, j], {j, 0, k}]*Binomial[n + k - 1, n - 1], {k, 1, n - 1}]/n;
%t Array[a, 24] (* _Jean-François Alcover_, Jul 23 2018 *)
%o (Maxima)
%o a(n):=sum((sum(binomial(j,n-3*k+2*j-1)*2^(k-j)*binomial(k,j),j,0,k))*binomial(n+k-1,n-1),k,1,n-1)/n;
%o (PARI) x='x+O('x^66); /* that many terms */
%o Vec(serreverse(x-x^2-x^3-2*x^4)) /* show terms */ /* _Joerg Arndt_, May 28 2011 */
%o (Magma) [&+[Binomial(i,n-3*k+2*i-1)*2^(k-i)*Binomial(k,i)*Binomial(n+k-1,n-1)/n: k in [0..25], i in [0..n]]: n in [1..25]]; // _Vincenzo Librandi_, Jul 23 2018
%K nonn
%O 1,3
%A _Vladimir Kruchinin_, May 28 2011